Classopollis works as a significant indicator for the Cheirolepidiaceae paleovegetation arid zone, as proven by fossil records from Egypt. - Ahmed Maher (PLoS ONE)
This paper presents an investigation that explores two distinct areas relatable to paleogeographic reconstruction. These areas include the Matruh Basin in the Northwestern Desert and the October Field in the Gulf of Suez in Egypt. The application of Scanning Electron Microscopy (SEM) has exposed the unique morphological attributes of Classopollis Pflug 1953, so simplifying improved understanding of new paleoecological interpretations relevant to the Mesozoic era. The Classopollis Pflug 1953 assemblage derived from four examined wells reveals significant similarities and is indicative of a uniform vegetative cover characterized by the Cheirolepidiaceae ecological zone. The results infer that the Classopollis Pflug 1953 assemblage may be a basis for biostratigraphic correlation within the coastal arid regions that adjoin the Tethys Sea. The genus Classopollis Pflug 1953 appears as a representative of the arid belt of the early Mesozoic and explains the expansion of the Cheirolepidiaceae family in coastal and desert areas, which suggests various adaptive strategies employed by this family. This study expresses the phylogenetic interconnections among the Cheirolepidiaceae, Tomaxellia, and Brachyphyllum while synchronously explaining the ecological effects and morphological evolution associated with Classopollis.